A reconfiguração da educação superior no Brasil e a formação profissional em Serviço Social: entre a contradição e as possibilidades de efetivação da formação crítica - Monteiro, Joselita Olivia da Silva (2016)
This work discuss the reconfiguration of higher education in Brazil and its relationship with professional training in social work. The theoretical approach is guided by Marxism. So to speak, affirms the education from the ontological character, and as such, arising from teleological positions derived from work, this understood as a category that founds the social being. For this study we used the bibliographical and documentary research in order to understand the changes occurring in higher education from the structural crisis of capital and training of social workers on this context. The study shows that from the reform of the Brazilian State started in the 1990s, the expansion of privatization of education is emphasized based on neoliberal adjustment policy, which tends to put it in the service of maintenance of profit rates, own this sociability. It appears that the way with education at the national level from its reconfiguration, effective the growth in the supply of social work courses in private higher education institutions. So, in an attempt to confront the deregulation of education, expressed mainly in the Law of Guidelines and Bases of Education - LDB, is founded by the Social Service the document: Guidelines Curriculum. In this understanding, this research lies the elements that typify the contradictions of this confrontation, and also notes that the changes occurring in education increasingly affect their subsumption to capital, either via its privatization, either by way of deregulation of public education. Therefore, it is stated that the main problem to be faced by education lies in the conditions that govern the existence of class society, given from the private ownership of the means of production. That is, that because of the position it occupies before the production process is the working class essentially antagonistic to capital, and therefore able to confront the capitalist sociability in order to effect a humanly emancipated society. In this sense, it is identified that the defense put under this profession, from the ethical-political project, although important, is situated on the very limits of political emancipation informed by Marx.